Detection of catechins in tea beverages using a novel electrochemical sensor based on cyclodextrin nanosponges composite. Issue 2 (15th February 2023) - Li, Yuhong; Chen, Xiaoling; Lin, Yueli; Yang, Yaqi; Zhang, Li; Zhao, Pengcheng; Wang, Chenxi; Fei, Junjie; Xie, Yixi
Abstract: Catechin (Cat) is one of the primary functional components of tea, and its accurate detection is significant for understanding the health benefits of tea. In this study, cyclodextrin nanosponges (CDNS) were prepared and employed to combine with graphene quantum dots (GQDs) and carboxylated multi‐walled carbon nanotubes (MWCNTs‐COOH) to form a CDNS/GQDs/MWCNTs‐COOH composite. Scanning electron microscope and X‐ray diffraction were used to characterize the composite which was used to build a new electrochemical Cat sensor. The abundance of cavities, intermolecular gaps, and surface active groups of CD molecules endowed CDNS with remarkable Cat enrichment capacity. Due to the outstanding biocompatibility of GQDs, the good electrocatalytic activity of MWCNTs‐COOH, and the enrichment capacity of CDNS, the composite modified glass carbon electrode (GCE) exhibited excellent electrochemical sensing performance. The CDNS/GQDs/MWCNTs‐COOH/GCE showed a sensitive peak current response to catechins in the linear range between 2 × 10 −8 and 1.2 × 10 −6 M, with a minimum limit of detection (S/N = 3) of 4.45 nM. The sensor has also been successfully applied for catechin detection in tea beverages. Abstract : A novel catechin electrochemical sensor has been developed based on the composite consisting of beta‐cyclodextrin nanosponge and carbon nanomaterials. The obtained sensor showed a rapid, stable, and sensitive detection performance for catechin even in real sample analysis of tea beverages.